Impact of Boardroom Gender Diversity on Firm Performance: Evidence from India - Khan, Yusra (2017)
Board diversity has become a major issue within corporate governance where a number of studies seek to explore the impact of diversity on firm performance. The debate focuses on questions such as whether a corporation’s board should reflect the firm’s stakeholders or be more in line with society in general. This article uses a sample of listed Indian firms during the period of 2009-2014. Despite that fact that India has gone very far in the liberalization of women, Indian board rooms are still to a large extent dominated by men. Contrary to a number of other studies, this article does not find any significant link between firm performance as measured by Tobin’s Q and Return on Assets (ROA) and female board representation.